Perancangan Atribut Produk Celana Denim Bobbiesjeans.Co Berdasarkan Preferensi Konsumen - Alan ramadhan; Yati Rohayati; Wawan Tripiawan (At-Tadbir : jurnal ilmiah manajemen, 2022)
Bobbiesjeans.co is an SME in Bandung that is engaged in fashion and has been established since 2017. The main product sold by Bobbiesjeans.co is denim pants, this is supported by the percentage of sales of around 74% compared to other products. The number of competitors who have more variations makes Bobbiesjeans.co denim pants products also experience ups and downs. Therefore, there is a need for innovation in Bobbiesjeans.co demin pants. The purpose of this study is to design the product attributes of Bobbiesjeans.co denim pants based on consumer preferences using the conjoint analysis method, product attributes for denim pants include model, material, color, leg opening width. Based on the results of the research that has been done, light blue can be added to the color. For the material, it is necessary to add a variety of poly denim (12 oz). Furthermore, for the waistline it is also necessary to add variations of low rise (below the waist) and mid rise (waist). Next to the model, it is necessary to add variations to the boot-cut model. And for arcuate it is also necessary to add variations of arcuate stitching.